Sejarah Dan Dinamika Pemikiran Hukum Islam - Fadholi, Ahmad (ASY SYAR'IYYAH: JURNAL ILMU SYARI'AH DAN PERBANKAN ISLAM, 2022)
Islamic law is part of the vast treasures of thought in Islam, in addition to thoughts in the fields of interpretation, Sufism, theology, and others. Since the 20th and 21st centuries, its existence has colored the religious attitudes of Muslims in various parts of the world. All matters relating to Islam are always judged by the standards of the laws that exist in Islamic law even though each country has its own positive law. This study uses a qualitative paradigm, with a library research approach. Sourced from the results of a search on the literature of classical fiqh books that contain the issue of differences of opinion of the fuqahā' about istinbāṭ hukm, as well as several contemporary books. The analysis used is content analysis (content analysis) through descriptive techniques, which are factual in the history of Islamic law, by understanding the verses of the Qur'an, hadith or the thoughts of scholars in formulating an idea of ​​Islamic law. The results of this study conclude that Islamic law as a product of Muslim thought in a fairly long history of existence must continue to be adapted to the demands of the times while maintaining its goal of creating benefit for mankind.